Liberty, Democracy and International Relations in Friedrich A. Hayek - Ferreira, Fernanda Gomes (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
The purpose of this article is to present some thoughts on the work of Friedrich A. Hayek, an important author of contemporary political theory. We will address some of the key points of his theory, including his concept of individual freedom, his reflections on democracy and the liberal state. We also intend, in the field of international relations, present the author’s views on the international order in the period after World War II.